Comparing the effect of knowledge management utilization on power and politics struggle with the mediator variable of influential groups - Reza Rasoli; Eskandar Shirazi; Hamed Masoudi (مدیریت مهندسی و رایانش نرم)
This research was conducted in the Educational Department of East Azerbaijan province in Iran and aimed at examining the effect of knowledge management on   power struggles. This applied study adopted a descriptive-survey design. The statistical population of this study contains all of the 1750 educational departments’ managers, supervisors and employees in East Azerbaijan province and multiple educational Districts in Tabriz. The stratified statistical sample of this study was selected by the category sampling method. Using the Cochran’s formula 380 individuals were randomly selected as the final sample of the study. The required data was collected by a questionnaire and the Amos software was employed to analyze data. Pearson correlation coefficient was utilized to test the hypothesis and path analysis was utilized for the model testing and assessing direct and indirect effect of the variables. The results of this study indicate that all of the components re-use of knowledge by others for similar needs, removal of the knowledge because of lack of credit change the shape of knowledge creation. It was also found that new knowledge and sharing tacit knowledge both affect power conflicts. The study also revealed that out of the aspects of power, the Removable power resource has the highest factor loadings (factor analysis) and Reduction of political appointees has the lowest correlation coefficient. Knowledge aspects was found to have a direct effect of 0/44 and an indirect effect of 0/57 on a power conflict through influential groups.